2013
DOI: 10.1371/journal.ppat.1003469
|View full text |Cite
|
Sign up to set email alerts
|

A Key Role for the Urokinase Plasminogen Activator (uPA) in Invasive Group A Streptococcal Infection

Abstract: Recruitment of the serine protease plasmin is central to the pathogenesis of many bacterial species, including Group A streptococcus (GAS), a leading cause of morbidity and mortality globally. A key process in invasive GAS disease is the ability to accumulate plasmin at the cell surface, however the role of host activators of plasminogen in this process is poorly understood. Here, we demonstrate for the first time that the urokinase-type plasminogen activator (uPA) contributes to plasmin recruitment and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Thus, covRS mutations enhance the ability of an isolate to activate plasminogen (255). In addition, it has recently been demonstrated that serotype M1T1 GAS strains utilize the host activator uPA to acquire cell surface plasmin in the absence of Ska and that this interaction also plays a role in a mouse model of invasive GAS disease (335).…”
Section: Subversion Of the Plasminogen Activation Systemmentioning
confidence: 99%
“…Thus, covRS mutations enhance the ability of an isolate to activate plasminogen (255). In addition, it has recently been demonstrated that serotype M1T1 GAS strains utilize the host activator uPA to acquire cell surface plasmin in the absence of Ska and that this interaction also plays a role in a mouse model of invasive GAS disease (335).…”
Section: Subversion Of the Plasminogen Activation Systemmentioning
confidence: 99%
“…It has been shown that the components of the uPA system are expressed in various types of hemopoietic cells ( 78 ). More importantly, their levels are altered during the course of infections suggesting the role of the uPA–uPAR system in mediating different types of immune response ( 87 89 ). In response to bacterial infection, proinflammatory cytokines such as TNF-α and IL-1β are released, which in turn increases uPA expression and secretion by different types of monocytes, neutrophils, epithelial and endothelial cells ( 87 ).…”
Section: Physiological Role Of the Upa–upar Systemmentioning
confidence: 99%
“…For example, the gram-negative bacteria Moraxella catarrhalis and Pseudomonas aeruginosa , as well as spirocytic bacteria Borrelia crocidurae and Borrelia burgdorferi , each bind plasminogen for host invasion (Singh et al, 2015; Ceremuga et al, 2014; Nordstrand et al, 2001; Gebbia et al, 1999; Coleman et al, 1995). In addition, gram-positive bacteria, such as Streptococcus pneumoniae , bind plasminogen and uPA to induce plasmin recruitment and initiation of bacterial invasion into the host while evading the normal innate immune response (Agarwal et al, 2013; Sanderson-Smith et al, 2013). Staphylococcus aureus , a gram-positive bacteria that causes infection of the skin and soft tissues, encodes its own plasminogen activator, staphylokinase, which induces plasmin activity and aids in invasiveness of S. aureus , inducing larger lesions in the host and decreased ability of the host to clear the bacteria (Peetermans et al, 2014).…”
Section: Plasminogen Plays a Role In The Development Of Many Pathologiesmentioning
confidence: 99%